Phosphorus recovery from sewage sludge ash with bioleaching and electrodialysis - ÇALLI, BARIŞ; SEMERCİ, NESLİHAN (ELSEVIER SCI LTD, 2019)
Phosphorus is an essential element for all living organisms and for plants. However, phosphate rock, which is the main source of phosphorus, is limited and thus it must be recovered from secondary sources like sewage sludge ash (SSA). SSA is one of the most promising secondary sources because it contains considerable amounts of phosphorus. The drawback of SSA as a secondary source is the presence of heavy metals along with phosphorus. In this study, a bioleaching process was applied to solubilize the phosphorus more economically, thus bioleaching bacteria was used to obtain acidic conditions for phosphorus leaching. For this purpose, batch bioleaching experiments were carried out with Sulfur oxidizing bacteria (SOB) to optimize the process in terms of phosphorus dissolution. Experiments were conducted with different amounts of ash, inoculum volumes, and sulfur concentrations. Because the application of the bioleaching process leads to solubilization of heavy metals beside phosphorus, an electrodialysis process was used to separate phosphorus from heavy metals. Electrodialysis experiments were performed in a 3 compartment electrodialysis reactor with gold coated copper electrodes. The maximum phosphorus bioleaching was obtained with 2 g of ash, 40% inoculum, and 10 g.l(-1) elemental sulfur. Electrodialysis studies with gold coated copper electrodes lasted for 14 days and 24.6% of the phosphorus was transported to the anode.
Keywords: Sewage sludge ash; Phosphorus recovery; Bioleaching; Sulfur oxidizing bacteria; Electrodialysis; HEAVY-METALS; ROCK PHOSPHATE; OXIDATION; SULFUR; SEPARATION; EXTRACTION; STRUVITE; WATER; IRON; ACID